PENGARUH MEDIA SOSIAL YOUTUBE TERHADAP PERILAKU KEAGAMAAN PEMUDA DESA BLANG PANYANG KECAMATAN MUARA SATU LHOKSEUMAWE - Rasma, Fachrina (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2024)
the influence of the use of Youtube social media on the religious behavior of youth in Blang Panyang village. this study is located in Blang Panyang Village, Muara Satu District, Lhokseumawe City. This study uses a quantitative approach with a correlational type of research. The population in this study was 437 people using the Taro Yamane formula so that a sample size of 81 people was obtained. The sampling technique used random sampling. The data collection technique in this study used a questionnaire / questionnaire. Meanwhile, to analyze the data in this study using a simple linear regression formula. The results showed that there was a significant influence between Youtube social media on religious behavior among the youth of Blang Panyang Village, Muara Satu District, Lhokseumawe City. regression test showed a significant influence between the independent variable X (use of Youtube social media) on religious behavior among the youth of Blang Panyang village. This is evidenced by the results of the T test as seen in the coefficient table with the dependent variable Y obtained the value of t count 3.396> t table 1.9904 and the significance level is 0.001 <0.05. the results of the F test also showed a significant effect, which can be seen from the ANOVA table, where in the F test, the dependent variable Y was obtained with a value of F count 11.534> F table 3.96. and seen from the significance value is 0.01 <0.05, from the results of the R then the coefficient of determination of the Youtube social media variable with the religious behavior variable (R Square) is 0.271. This shows that the religious behavior of youth in Blang Panyang village is influenced by the use of Youtube social media around 27.1%.